Temperature and moisture effects on the failure of composites - Lui, Man To (2018)
Composite tidal turbine blades are subjected to seawater degradation and mechanical loadings from the operating environment. However, there is limited research on the effects of moisture and voids on the mechanical properties of composite made using Vacuum Assisted Resin Transfer Method (VARTM). Hence, this project will further explore the correlation between void, moisture and strength of composite material, fabricated from T300 Carbon Fibers and Epikote RIMR 135 resin. The main purpose of this project is to analyse the tensile and flexural properties of Carbon Fiber Reinforced Polymer (CFRP) composite through static tensile and 3-point flexural tests.